Hungarian male water polo players' body composition can predict specific playing positions and highlight different nutritional needs for optimal sports performance - Fritz, P.; Fritz, R.; Mayer, L.; Németh, B.; Ressinka, J.; Ács, P.; Oláh, C. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background Water polo is unique among aquatic—and generally other—sports as it includes cyclic elements typical in swimming and acyclic elements occurring mainly in ball games. Moreover, water polo demands high level of technical and tactical skills. Players need an optimal nutritional and physical condition to achieve high athletic performance, which is to a great extend influenced by nutritional habits. We aim to highlight possible shortfalls in players` nutritional intake in relation to positions played within the team.